Sexual Anatomy - Ulrich, Monica; Bigler, Mark (TRAILS: Teaching Resources and Innovations Library for Sociology, 2011)
Purpose: To learn the sex differences between men and women, to learn which sex people are more familiar and comfortable with, to learn how to use precise sexual language in a classroom setting. Time: 20 minutes Preparation: Prepare note cards. Each note card should have a part of the male or female anatomy on it. Number of students: This exercise works well with up to 30 students. If there are more, the class needs to be divided.